Effect of temperature in the process of magnetic nanoparticle coprecipitation - Ramos, Victor Crepaldi; Michelotti, Michel Augusto Massambani; Pinto, Edilson Moura; Kinoshita, Angela (Revista Hipótese, 2019)
Several methods of synthesis and protection in magnetic cores,superfice functionalization has been studied, in order to improve of application. This work investigated the synthesis of iron oxide nanoparticles by coprecipitation, evaluating the effects of temperature. The nanoparticles were evaluated by different techniques to measure the radius and magnetic force. The results obtained showed to us the better synthesis was using temperature among 40-55 ºC.
Keywords: Magnetic nanoparticles; Temperature; Coprecipitation